Frequency Of Brain Atrophy Diagnosed on Computed Tomography: Frequency of Brain Atrophy Diagnosed on Computed Tomography - Munir, Humayun; Arshad, Nosheen; Ali, Abid; Jamil, Mariam; John, Akash (Pakistan Journal of Health Sciences, 2022)
Brain atrophy is the loss of connections between neurons. It can be due to old age, trauma, ischemic stroke, multiple sclerosis, post infective and neurodegenerative diseases. Objective: To determine the frequency of brain atrophy on Computed Tomography. Methods: A cross sectional study conducted in Medcare international hospital, Gujranwala and DHQ, Kasur. The data was collected using convenient sampling technique from February 2022 to May 2022 after written consent. A sample size of 60 was calculated using mean from previous published studies. The age considered was maximum of 100 and minimum of 20 years. The study included all the patients who had focal and generalized brain atrophy. The equipment used for the evaluation was Toshiba Aquilion 64 slices CT scanner. Results: The mean age of patients was 79.88 ± 9.22 having minimum age of 57y and maximum age of 91y. The male patients were more frequent as 34(56.7%) and females as 26(43.3%). The brain atrophy was categorized as focal 14(23.3%) and generalized atrophy 46(76.7%). The patients of brain atrophy had history of smoking 30(39%), alcohol use 13(16.9%) and diabetes mellitus 15(19.5%) and the common symptoms include memory problems 25(33.3%), poor judgment 13(17.3%) and loss of language 11(14.7%). The most common cause of brain atrophy evaluated was due to old age 42(70%) following post traumatic 9(15%) and Alzheimer 4(6. 7%). Conclusion: In conclusion, brain atrophy can be due to old age, trauma and Alzheimer disease. The common symptoms include memory problems and loss of language.